Análisis documental sobre el tema del big data y su impacto en los derechos humanos - Téllez Carvajal, Evelyn (2020)
The aim of this article is to provide the reader a documentary record on the subject of the technological infrastructure and the knowledge management of big data analytics and their relation to human rights. Currently, human rights violations around the world due to the indiscriminate use of big data analytics is a constant, since the information that is generated every day and every second by the use of technological devices —such as smartphones— makes possible the collection of information, that goes from consumption data to even private information, such as religious opinions or biometric data. Human rights violations due to big data analytics starts by the way personal data is collected and treated. Sometimes people do not know how their data are being processed, stored or used.As a result of the analysis, it was observed that several articles, books and papers refer to personal data and privacy regulations, focusing in the regulations of the data mining conditions. Despite, those regulations, it can be observed that big data analytics could allow a wide margin for infringement of not only the human right to privacy, but also of another human rights; for instance, through actions that promote racism, the creation of blacklists, the promotion of segregation and the limit of the freedom of speech, just to mention some examples.